Mind Over Matter - Time-Life Books INC.; Editor: George Constable (Alexandria Time-Life Books, 1991)
Examines paranormal phenomena such as poltergeists, psychokinesis, and mind control.
Include Index, Bibliography and Colour Illustration
Keywords: Psychokinesis. -- Theatrical agents -- Motion picture producers and directors